2007
DOI: 10.1007/s10886-007-9382-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Different Wheat Genotypes During Attack by Virulent and Avirulent Hessian Fly (Mayetiola destructor) Larvae

Abstract: Wheat and its relatives possess a number of resistance (R) genes specific for the Hessian fly (HF) [Mayetiola destructor (Say)]. HF populations overcome R gene resistance by evolving virulence. Virulent HF larvae manipulate the plant to produce a nutritionally enhanced feeding tissue and, probably, also suppress plant defense responses. Using two wheat R genes, H9 and H13, and three HF strains (biotypes) differing in virulence for H9 and H13, we conducted a genome-wide transcriptional analysis of gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
84
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 59 publications
8
84
0
Order By: Relevance
“…6E). Previous transcriptomic studies have reported that cellulose synthase and other cell-wall modification genes were altered after sensing phloem feeding herbivores [65,[78][79][80] and hormones JA and SA [81]. Our data identified three cell wall degradation related transcripts that are putatively associated with polygalacturonase (pectinases) altered within 24 and 48 hai (Fig.…”
Section: Cell Wall Modificationmentioning
confidence: 55%
“…6E). Previous transcriptomic studies have reported that cellulose synthase and other cell-wall modification genes were altered after sensing phloem feeding herbivores [65,[78][79][80] and hormones JA and SA [81]. Our data identified three cell wall degradation related transcripts that are putatively associated with polygalacturonase (pectinases) altered within 24 and 48 hai (Fig.…”
Section: Cell Wall Modificationmentioning
confidence: 55%
“…The SSPs likely act in plant-insect interactions and might be valid regulators of gall development (Zhang et al 2010). A gall insect can restrain plant growth, reprogram plant gene transcription, and stimulate nutritive tissues (Anderson and Harris 2006;Harris et al 2006;Liu et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…ROS are likely involved in plant defense against other galling insects, because plant hypersensitive symptoms have been observed during these interactions (Chen, 2008). In addition to ROS, other likely defense chemicals reported in the literature include lectins (Subramanyam et al, 2006), inhibitors of digestive enzymes (Wu et al, 2008), and secondary metabolites (Liu et al, 2007). A combination of toxic defense chemicals accumulated at the attack site is the likely cause for the death of Hessian fly larvae within resistant plants.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in levels of transcripts and, in some cases, encoded proteins of many defense-related genes such as those encoding digestive enzyme inhibitors (Wu et al, 2008), lectins (Williams et al, 2002;Subramanyam et al, 2006Subramanyam et al, , 2008Giovanini et al, 2007), and enzymes for the biosynthesis of secondary metabolites (Liu et al, 2007) indicates that a combination of defense chemicals may be involved in resistance to Hessian fly. During compatible interactions (wheat infested with virulent larvae), susceptible plants are manipulated by Hessian fly larvae, including the suppression of plant defense Saltzmann et al, 2010) and the reprogramming of plant metabolic pathways to create a nutrition zone for larval development (Puthoff et al, 2005;Harris et al, 2006;Liu et al, 2007;Saltzmann et al, 2008;Zhu et al, 2008). The manipulation of plants by Hessian fly larvae is likely achieved through salivary secretions (Chen et al, 2004, which may also trigger plant defense if recognized by the plant surveillance system (Garcia-Brugger et al, 2006).…”
mentioning
confidence: 99%